STRATEGIC MANAGEMENT ACCOUNTING (SMA) USAGE, MANAGERS’ MENTAL HEALTH AND FIRM PERFORMANCE: AN EXPERIMENTAL STUDY - Sahla, Widya Ais; Arief, Khozin; Bahit, Muhammad (Jurusan Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Mataram, 2025)
Based on RBV’s theory, SMA Usage and employee mental health are valuable internal resources that can offer a competitive advantage when managed effectively. This research explores their impact on firm performance and highlights their importance to organizations. This is an experimental study with a 2x2 factorial design between subjects by manipulating SMA Usage (strong and weak) and the manager's mental health (high and low). This study found that SMA Usage and managers' mental health are key factors in firm performance, with the interaction effect evident only in net profit. The findings also support RBV theory, showing that both are crucial for firms to manage effectively. This study offers valuable practical implications for companies aiming to enhance performance. Effective SMA implementation supports strategic decisions, while prioritizing managers' mental health promotes strong leadership, both contributing to sustainable competitive advantage. To the best of the authors' knowledge, this is the first study that combined the field of strategic management accounting with the field of psychology to examine the effects on firm performance. The experimental approach is also a novelty to test the causality of the two factors